(untitled) (Revista de Ciências Agroveterinárias, 2023)
The objective of this work was to verify the influence of different colors of shading nets in the cultivation and postharvest of Physalis in an organic production system. The experiment was carried out in the experimental area of the Universidade Federal da Fronteira Sul (UFFS), Laranjeiras do Sul – PR, in the Horticulture sector. As plant material, we used seedlings of Physalis peruviana L., produced in an agricultural greenhouse in the experimental teaching area of UFFS. The experimental design adopted in the field was in completely randomized blocks, in a one-factor scheme of four shading nets: blue, black, red, white + control, without coverage. For the phenology, there was no statistical influence of the coloring shade nets on this variable.Plants with greater height and smaller diameter were verified using the blue color shading net. The plants that were on the black printing net had a lower height. There were distinct changes in fruit firmness, mass with calyx, diameter, height and soluble solids. It is concluded in this work that shading nets of different colors affect the physicochemical characteristics of Physalis peruviana fruits, however, some colorations are not viable to be used.